Risk Ananlysis and Estimation of Scheduling of Software Project – Using Stochastic Approach - Bindra, Yogita; Garg, Rajesh; Kaur, Navneet (International Journal of Computer Sciences and Engineering, 2025)
A project is a combination of several interrelated activities which must be performed in a certain order of its completion. To meet tight deadlines in software projects, managers need to understand key reservations about the scheduling techniques and how to use a schedule risk analysis to provide information crucial to a project’s success. This paper describes an application of simulation which simulates the duration of the activities for analyzing schedule risk and providing reliable estimates of time. Monte Carlo Simulation Methods are mostly used for analyzing schedule risk. In this the random numbers are generated to simulate the software project number of times. The primary objective of the simulation is to find out the effect of uncertainties on the schedule of project completion. The designed simulator SRAES for a live website Filmtribe uncovered the critical paths and risky activities in the project and also provided the risk indices of those risky activities. The simulator also calculated the Project Completion Time in less than 1 minute which can take months to calculate analytically. Therefore, it is concluded that Monte Carlo Simulation is an important technique for risk analysis and estimation of scheduling in any type of software projects.